2010
DOI: 10.19030/tlc.v7i11.252
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts Of Cooperative Learning On Anxiety And Proficiency In An EFL Class

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 3 publications
(3 reference statements)
2
30
1
Order By: Relevance
“…This finding is partly consistent with Zhou et al's (2005) study on Chinese graduate students studying in Canada, which concluded that they seldom participate in class due to their unfamiliarity with the interaction format in Canada and the lack of background knowledge of Canadian culture. This finding is inconsistent with Young's (1990) and Suwantarathip and Wichadee's (2010) study which concluded that students who work in small groups experience low anxiety.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This finding is partly consistent with Zhou et al's (2005) study on Chinese graduate students studying in Canada, which concluded that they seldom participate in class due to their unfamiliarity with the interaction format in Canada and the lack of background knowledge of Canadian culture. This finding is inconsistent with Young's (1990) and Suwantarathip and Wichadee's (2010) study which concluded that students who work in small groups experience low anxiety.…”
Section: Discussioncontrasting
confidence: 82%
“…Besides all of the factors mentioned above, many other factors such as learners' self-confidence (Clément;1980;Casado & Dereshiwsky, 2004), language self (Horwitz, et al, 1986), tolerance of ambiguity (Ehrman & Oxford, 1995), unwillingness to communicate (Liu & Jackson, 2008), fear of speaking (Horwitz et al, 1986;Mak, 2011), attitudes toward language classes (Aida, 1994;Mak, 2011), fear of failing the language class (Aida, 1994;Mak, 2011), teachers' attitudes or characteristics (Young, 1990), teaching pedagogies (Suwantarathip & Wichadee, 2010;Young, 1990Young, , 1999, etc., are all found to be associated with FL or SL anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that there were no statistically significant differences between pretest and posttest scores. Suwantarathip and Wichadee [8] studied the impacts of cooperative learning on anxiety and proficiency in an English class using cooperative learning strategy. The Standardized Foreign Language Classroom Anxiety Scale and two proficiency tests covering reading and writing skills, respectively, were used as the outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…The reason why their anxiety decreased was probably because this learning environment provided opportunities for students to support, encourage, and praise each other. In such an atmosphere, students may feel more relaxed to try out new ideas (Suwantarathip & Wichadee, 2010(. From the results presented in this chapter, it seems clear that the students viewed CR group discussions to be a valuable learning tool, especially as they became more comfortable with each other. Student-led literature discussion is…”
Section: Discussionmentioning
confidence: 87%